Detection of influenza D virus in respiratory disease samples from Northern Irish cattle. Issue Volume 1(2019)Issue A (8th March 2019) - Dane, Hannah; Duffy, Catherine; Guelbenzu, Maria; Hause, Ben; Fee, Sean; McConnell, Shirley; Forster, Fiona; McMenamy, Michael; Lemon, Ken
Abstract : Influenza D virus (IDV) is a newly described member of the Orthomyxoviridae family, initially identified during a 2011 outbreak of respiratory disease in North American pigs. Cattle were subsequently shown to be the main reservoir of the virus and accumulating evidence suggests a role for IDV in bovine respiratory disease complex. During the winter of 2017/2018, cattle submitted to the Agri-Food and Biosciences Institute for post-mortem with confirmed respiratory disease were tested for the presence of IDV by real-time RT-PCR. Virus isolation was performed in Swine Testes cells and full-genome sequence determined. Of 104 cattle with confirmed respiratory disease, 9 tested positive for IDV (8.7 % prevalence). Virus was detected in both the upper and lower respiratory tract. Lung tissues from IDV positive samples were negative for the presence of bovine herpesvirus 1, bovine respiratory syncytial virus, bovine viral diarrhea virus and parainfluenza virus 3. Of the 9 cattle which tested positive for IDV, 3 tested positive for coronavirus. Histological analysis of lungs from IDV positive samples revealed pathological features including necrosis, neutrophil infiltration of alveolar spaces, fibrosis, congestion, oedema and haemorrhage. Sequenced isolates were shown to cluster with European isolates of the D/swine/Oklahoma/1334/2011 clade. To date, IDV has been detected in North America, Mexico, Japan, China, France, Italy and the Republic of Ireland. This study is the first to identify IDV in UK cattle herds. The presence of IDV in respiratory disease samples supports a role for this virus in bovine respiratory disease complex.